2018
DOI: 10.1093/jas/sky187
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters of methane emissions determined using portable accumulation chambers in lambs and ewes grazing pasture and genetic correlations with emissions determined in respiration chambers1

Abstract: Methane (CH4) emission traits were previously found to be heritable and repeatable in sheep fed alfalfa pellets in respiration chambers (RC). More rapid screening methods are, however, required to increase genetic progress and to provide a cost-effective method to the farming industry for maintaining the generation of breeding values in the future. The objective of the current study was to determine CH4 and carbon dioxide (CO2) emissions using several 1-h portable accumulation chamber (PAC) measurements from l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
98
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(120 citation statements)
references
References 28 publications
(66 reference statements)
13
98
9
Order By: Relevance
“…On the other hand, the residual of CO 2 from MBW and ADG (r wg CO 2 ) was not related to RFI (R p = 0.04 and 0.10), whereas Arthur et al [31] found a low and significant correlation: R p = 0.27. The correlations of the CH 4 /CO 2 ratio with CH 4 were R p = 0.58 and 0.61, the same values obtained by Herd et al [18] with yearling beef animals measured with GreenFeed (R 2 = 0.40) and Jonker et al [29] with lambs measured in respiratory chambers, R p = 0.65. The correlations of CH 4 /CO 2 with CH 4 /DMI were low, R p = 0.24 and 0.33, much lower than the estimates obtained by Herd et al [18] (R 2 = 0.49) and Jonker et al [29], R p = 0.84.…”
Section: Calculated Growth and Methane Efficiency Traits Adjusted Forsupporting
confidence: 82%
See 2 more Smart Citations
“…On the other hand, the residual of CO 2 from MBW and ADG (r wg CO 2 ) was not related to RFI (R p = 0.04 and 0.10), whereas Arthur et al [31] found a low and significant correlation: R p = 0.27. The correlations of the CH 4 /CO 2 ratio with CH 4 were R p = 0.58 and 0.61, the same values obtained by Herd et al [18] with yearling beef animals measured with GreenFeed (R 2 = 0.40) and Jonker et al [29] with lambs measured in respiratory chambers, R p = 0.65. The correlations of CH 4 /CO 2 with CH 4 /DMI were low, R p = 0.24 and 0.33, much lower than the estimates obtained by Herd et al [18] (R 2 = 0.49) and Jonker et al [29], R p = 0.84.…”
Section: Calculated Growth and Methane Efficiency Traits Adjusted Forsupporting
confidence: 82%
“…The two emission rates were also highly correlated with the heifer body weight, slightly more for CO 2 (R p = 0.77 and 0.85) than for CH 4 (R p = 0.68 and 0.70). Similar results were obtained with dairy cows [30] and yearling beef cattle [14,31,32] measured with GreenFeed systems or with yearling beef cattle [5] and lambs [29] measured in respiratory chambers: R p = 0.57 to 0.74 for the correlation between CH 4 and BW and R p = 0.71 to 0.87 for the correlation between CO 2 and BW. In ruminants, DMI and gross energy intake (GEI) are considered to be the predominant drivers of enteric methane production [33].…”
Section: Recorded Traitssupporting
confidence: 81%
See 1 more Smart Citation
“…In addition, respiration chambers reflect an artificial environment, which is not representative of sheep kept in pasture-based production systems. Animals might show abnormal behavior (e.g., reduced dry matter intake, DMI) in the chamber, possibly influencing a CH 4 emission pattern (Kabreab et al, 2006;Bickell et al, 2014). Thus, Knapp et al (2014) and Huhtanen et al (2015) requested alternative reliable and cost-efficient methods for CH 4 recording, especially under field conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In such a context, approaches based on feed supplements were unsuitable under grazing conditions (Baker, 1999). Predictions of CH 4 via deterministic modeling usually require a large amount of input data, e.g., DMI, dietary or milk components, which are difficult to record (Kabreab et al, 2006;Yin et al, 2015). Further indirect methods for CH 4 emission predictions based on the ruminal microbiome composition but associations between CH 4 production and microbiome characteristics were inconsistent (Shi et al, 2014;Ellison et al, 2017).…”
Section: Introductionmentioning
confidence: 99%